PENGARUH INTERNET FINANCIAL REPORTING, EARNING POWER, INVESTMENT OPPORTUNITY SET TERHADAP COST OF EQUITY CAPITAL DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2015) - Wati, Yenny; Rasuli, M; L, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to examine the effect of direct and indirect consequences of internet financial reporting, earning power, and the investment opportunity set in cost of equity capital with earnings management as intervening variable. Collecting data using a purposive sampling method for manufacturing companies listed on the Indonesia Stock Exchange in 2010-2015 which is analyze by path analysis. The results show that: (1) the Price earning ratio and investment to sales have a direct effect on the cost of equity capital, (2) Content, timeliness, utilization of technology, user support, net profit margin, return on assets, market to book equity, capital to total assets, and earnings management did not have a direct effect on the cost of equity capital, (3) Content, timeliness, net profit margin, return on assets, and the price earning ratio has a direct effect on earnings management, (4) the utilization of technologies, user support, market to book equity, investment to sales, and capital to total assets has no direct effect on earnings management, (5) Content, timeliness, utilization of technology, user support, net profit margin, return on assets, market to book equity, price earning ratio, investment to sales, and capital to total assets does not have indirectly effect on the cost of equity capital through earnings management.Keywords: Cost of Equity Capital, Earnings Management, Internet Financial Reporting, Earning Power, Investment Opportunity Set